The archeology and origin myth of the Shipibo-Conibo from Peruvian Amazon - Morales Chocano, Daniel (2019)
The article confirms the ethnographic evidence on the myth of origin of the Shiibo-Conibo with the material archaeological culture of the basin of the Ucayali in the Peruvian Amazonía, coming to interesting conclusions.